Randomized investigation of increased dialyzer membrane hydrophilicity on hemocompatibility and performance - Ehlerding, Götz; Ries, Wolfgang; Kempkes-Koch, Manuela; Ziegler, Ekkehard; Ronová, Petra; Krizsán, Mária; Verešová, Jana; Böke, Mária; Erlenkötter, Ansgar; Nitschel, Robert; Zawada, Adam M; Kennedy, James P; et al. (BMC nephrology, 2024)
BACKGROUND: Hemodialyzers should efficiently eliminate small and middle molecular uremic toxins and possess exceptional hemocompatibility to improve well-being of patients with end-stage kidney disease. However, performance and hemocompatibility get compromised during treatment due to adsorption of plasma proteins to the dialyzer membrane. Increased membrane hydrophilicity reduces protein adsorption to the membrane and was implemented in the novel FX CorAL dialyzer. The present randomized controlled trial compares performance and hemocompatibility profiles of the FX CorAL dialyzer to other commonly used dialyzers applied in hemodiafiltration treatments. METHODS: This prospective, open, controlled, multicentric, interventional, crossover study randomized stable patients on post-dilution online hemodiafiltration (HDF) to FX CorAL 600, FX CorDiax 600 (both Fresenius Medical Care) and xevonta Hi 15 (B. Braun) each for 4 weeks. Primary outcome was β2-microglobulin removal rate (β2-m RR). Non-inferiority and superiority of FX CorAL versus comparators were tested. Secondary endpoints were RR and/or clearance of small and middle molecules, and intra- and interdialytic profiles of hemocompatibility markers, with regards to complement activation, cell activation/inflammation, platelet activation and oxidative stress. Further endpoints were patient reported outcomes (PROs) and clinical safety. RESULTS: 82 patients were included and 76 analyzed as intention-to-treat (ITT) population. FX CorAL showed the highest β2-m RR (76.28%), followed by FX CorDiax (75.69%) and xevonta (74.48%). Non-inferiority to both comparators and superiority to xevonta were statistically significant. Secondary endpoints related to middle molecules corroborated these results; performance for small molecules was comparable between dialyzers. Regarding intradialytic hemocompatibility, FX CorAL showed lower complement, white blood cell, and platelet activation. There were no differences in interdialytic hemocompatibility, PROs, or clinical safety. CONCLUSIONS: The novel FX CorAL with increased membrane hydrophilicity showed strong performance and a favorable hemocompatibility profile as compared to other commonly used dialyzers in clinical practice. Further long-term investigations should examine whether the benefits of FX CorAL will translate into improved cardiovascular and mortality endpoints. TRIAL REGISTRATION: eMPORA III registration on 19/01/2021 at ClinicalTrials.gov (NCT04714281).
Keywords: Kidney Failure, Chronic; klinické křížové studie; Humans; lidé středního věku; membrány umělé; Hydrophobic and Hydrophilic Interactions; Female; Aged; senioři; lidé; hemodiafiltrace; ženské pohlaví; chronické selhání ledvin; Male; Middle Aged; Membranes, Artificial; beta 2-Microglobulin; beta-2-mikroglobulin; Cross-Over Studies; mužské pohlaví; prospektivní studie; Hemodiafiltration; hydrofobní a hydrofilní interakce; Prospective Studies